2020
DOI: 10.3390/v12050571
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular Vesicles as Allies of HIV, HCV and SARS Viruses

Abstract: Extracellular vesicles (EVs) are lipid bilayer-enclosed entities containing proteins and nucleic acids that mediate intercellular communication, in both physiological and pathological conditions. EVs resemble enveloped viruses in both structural and functional aspects. In full analogy with viral biogenesis, some of these vesicles are generated inside cells and, once released into the extracellular milieu, are called “exosomes”. Others bud from the plasma membrane and are generally referred to as “microvesicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 173 publications
0
36
0
1
Order By: Relevance
“…During cellular infection, some viruses may use this machinery by packing viral proteins and RNA into vesicles that are later released to the extracellular space, thereby contributing to the spread of the virus to non-infected cells [10]. This has been shown for HIV [39] but has not yet been elucidated for coronaviruses [40]. Another is their heterogeneity, since EVs are diverse in origin, size, composition, and functional characteristics; therefore, the choice of their source for therapeutic use should be carefully elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…During cellular infection, some viruses may use this machinery by packing viral proteins and RNA into vesicles that are later released to the extracellular space, thereby contributing to the spread of the virus to non-infected cells [10]. This has been shown for HIV [39] but has not yet been elucidated for coronaviruses [40]. Another is their heterogeneity, since EVs are diverse in origin, size, composition, and functional characteristics; therefore, the choice of their source for therapeutic use should be carefully elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar considerations also apply to the EVs released during coronavirus infection. EVs are lipid bilayer-enclosed structures released by cells into the extracellular environment, which can be divided into three subgroups: exosomes (30–150 nm), microvesicles (50–1,000 nm) and apoptotic bodies (50 nm to 5 μm) (Giannessi et al, 2020 ). It has been shown that infections caused by HIV and HCV induce the release of EVs to create a proviral environment, but the relationship between coronaviruses and EVs is not fully characterized (Giannessi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVs are lipid bilayer-enclosed structures released by cells into the extracellular environment, which can be divided into three subgroups: exosomes (30–150 nm), microvesicles (50–1,000 nm) and apoptotic bodies (50 nm to 5 μm) (Giannessi et al, 2020 ). It has been shown that infections caused by HIV and HCV induce the release of EVs to create a proviral environment, but the relationship between coronaviruses and EVs is not fully characterized (Giannessi et al, 2020 ). In one study, overexpressed SARS-CoV S protein was not readily detected in the pelleted exosomes, unless the transmembrane and cytoplasmic domains were replaced by those of VSV-G (Kuate et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human host factor angiotensin-converting enzyme 2 (ACE2) has been identified, during the first coronavirus epidemic, as the receptor for the SARS causing coronavirus [ 129 ]. ACE2 and the DC-SIGN family of receptors bind the S protein, mediating coronavirus entry to target cells [ 125 ].…”
Section: Role Of Evs In the Pathogenesis Of Viral Infectionsmentioning
confidence: 99%